(untitled) (Al-Qamar, 2021)
Migration is the ancient sunnah of all the prophets (A.S) .Hazrat Muhammad ﷺ also migrated to Madina because of the atrocities committed by Makkans, their less inclination to Islam and the command (order) of Allah .Migration is done to achieve great objects and it results in lot of benefits .One of them is establishment of peace. The people who migrate , get rid of cruelties of natives .In this sense, it is a source of peace for immigrants as it happened with the immigrants of migration of (Abyssinia) and Madina .Islamic state was established after ‘Madina Migration’ .In this way, the natives and others nations enjoyed the establishment of peace .There are many aspects of this establishment of peace as uniformity of human race, elimination of riots, unification and cooperation, justice system, educational referms , security of fundamental rights , legal retribution and implementation of Hdood, Blood money and beginning of accountability .The international relations and issues after migration all these phenomenon become the source of establishment of peace . Blessings of Medina migration were not only source of peace for the people of this era but also for the whole humanity.